PENENTUAN BIDANG MINAT TUGAS AKHIR MAHASISWA TEKNIK INFORMATIKA UNIVERSITAS ISLAM MADURA MENGGUNAKAN METODE K-MEANS - Nurul Badriyah; Hozairi; Miftahul Walid (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Selection of areas of interest can be confusing for some students, so data grouping or clustering is needed for informatics engineering students as a determinant of the field of interest for the final project. The purpose of this study is to group data or clustering on informatics engineering students as a determinant of the field of interest in the final assignment based on course grades. The method to be used is k-means clustering, to determine the number of clusters in the final project interest grouping. After the trial process was carried out, the results obtained showed that the number of clusters was 3 clusters, where in this grouping process, it can be concluded that the majority of students (60%) have an interest in the SPK course. While the field of interest in IS is only owned by around 20% of students, and the field of interest in Data Mining is only owned by around 6% of students. Therefore, it can be said that students tend to have a stronger interest in the SPK field based on the calculation results of the grouping or clustering process.